Electrical, structural, thermal and electrochemical properties of corn starch-based biopolymer electrolytes. (25th June 2015) - Liew, Chiam-Wen; Ramesh, S.
Highlights: Biopolymer electrolytes exhibit VTF relationship. Addition of ionic liquid in polymer electrolytes reduces T g . Ionic liquid-doped polymer electrolyte has better electrochemical properties of EDLC. Abstract: Biopolymer electrolytes containing corn starch, lithium hexafluorophosphate (LiPF6 ) and ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate (BmImPF6 ) are prepared by solution casting technique. Temperature dependence-ionic conductivity studies reveal Vogel–Tamman–Fulcher (VTF) relationship which is associated with free volume theory. Ionic liquid-based biopolymer electrolytes show lower glass transition temperature ( T g ) than ionic liquid-free biopolymer electrolyte. X-ray diffraction (XRD) studies demonstrate higher amorphous region of ionic liquid-added biopolymer electrolytes. In addition, the potential stability window of the biopolymer electrolyte becomes wider and stable up to 2.9 V. Conclusively, the fabricated electric double layer capacitor (EDLC) shows improved electrochemical performance upon addition of ionic liquid into the biopolymer electrolyte. The specific capacitance of EDLC based on ionic liquid-added polymer electrolyte is relatively higher than that of ionic liquid-free polymer electrolyte as depicted in cyclic voltammogram.